2014
DOI: 10.1016/j.annepidem.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association of urinary bisphenol-A concentration with selected indices of glucose homeostasis among U.S. adults

Abstract: Purpose Emerging evidence suggests that exposure to endocrine disruptors may initiate or exacerbate adiposity and associated health problems. This study examined sex differences in the association of urinary level of bisphenol-A (BPA) with selected indices of glucose homeostasis among U.S. adults. Methods Data analyses were performed using a sample of 1,586 participants from the 2005–2008 National Health and Nutrition Examination Surveys. BPA level and the ratio of BPA-to-creatinine level were defined as log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 60 publications
4
44
0
Order By: Relevance
“…These results further indicated that BPA may disrupt blood glucose homeostasis and damage pancreas function in STD-and HFD-fed rats. The increased insulin resistance and disrupted glucose homeostasis reported in the rodents of the study of Alonso-Magdalena et al (2006) and our present study were also reported by Beydoun et al (2013) in adults in the USA with higher BPA burden.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These results further indicated that BPA may disrupt blood glucose homeostasis and damage pancreas function in STD-and HFD-fed rats. The increased insulin resistance and disrupted glucose homeostasis reported in the rodents of the study of Alonso-Magdalena et al (2006) and our present study were also reported by Beydoun et al (2013) in adults in the USA with higher BPA burden.…”
Section: Discussionsupporting
confidence: 74%
“…To limit the bias of misclassification, circulating levels of fasting glucose and insulin were used to study the association of BPA and insulin resistance. Recently, positive associations of BPA levels with insulin resistance have been observed in middleaged and elderly Chinese adults (Wang et al 2012), as well as in adults in the USA (Beydoun et al 2013). Furthermore, a positive association of urinary BPA levels with pre-diabetes among non-diabetic adults in the USA has been reported by Sabanayagam et al (2013).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies in animal models as well as human epidemiological studies have shown that some EDCs can impair pancreatic ␤-cell function and induce insulin resistance at concentrations found in human plasma (2,3). Thus, there is growing concern that EDCs may act as diabetogenic agents and elicit important metabolic disorders, including diabetes (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Global insulin resistance associated with MDC exposure is supported by epidemiologic, animal, and molecular studies [5]. Human exposures to a wide variety of chemicals have been associated with insulin resistance, including BPA [42,43], particulate matter (PM) [44], 2,3,7,8-tetrachlorodibenzo dioxin (TCDD) [45], and phthalates [46,47]. The precise mechanisms by which these chemicals promote insulin resistance are discussed below.…”
Section: Disruption Of Insulin Actionmentioning
confidence: 99%